Sleeping with the enemy: case reports of Ornithonyssus bursa (Berlese, 1888) (Mesostigmata: Macronyssidae) causing human dermatitis in Brazil - Bassini-Silva, Ricardo [UNESP] (2022)
Ornithonyssus bursa, known as the “tropical fowl mite,” is a hematophagous mite of domestic and wild birds, which occasionally bites humans. Accidental bites on humans occur mainly when abandoned bird nests are close to homes or when people are handling parasitized birds. In the present study, we describe five case reports of bites on humans and new records of localities for this species. Based on the material examined, we provide morphological and molecular characterizations for this species herein.